Socio-demographic variation in chest pain incidence and subsequent coronary heart disease in primary care in the United Kingdom. (29th August 2020) - Walters, Kate; Rait, Greta; Hardoon, Sarah; Kalaitzaki, Eleftheria; Petersen, Irene; Nazareth, Irwin
Abstract: Background: We know little about socio-demographic differences in chest pain presenting to primary care and subsequent coronary heart disease (CHD) diagnosis. Methods: We conducted a cohort study with 198, 209 patients aged 30 years and over with a first episode of chest pain, using data from 339 general practices in The Health Improvement Network (THIN) primary care database during 1997–2007. We calculated incidence of chest pain and subsequent CHD by age, gender and quintiles of Townsend area deprivation score. Results: Chest pain incidence was 19.6/1000 person years at risk (PYAR, 95% CI 19.5–19.7). Incidence rose with age and increasing deprivation, with minimal gender differences. The incidence of CHD in the year following chest pain in primary care was 96.6/1000 PYAR (95% CI 95.1–98.0). There were significant interactions with age/deprivation and gender/deprivation on subsequent CHD diagnosis. The effect of deprivation was less for those over 60 years, and greater for younger women. Women in their 30s with chest pain in deprived areas had 8.77 times (95% CI 3.34–23.06) the CHD incidence compared to those in the most affluent areas. The absolute risk difference was small (8/1000 PYAR, 95% CI 4.5–11.5/1000 PYAR). Conclusions: There was a modestly greater incidence of chest pain in primary care in more deprived areas compared to the least deprived areas. There were interactions between age, gender and deprivation on subsequent CHD diagnosis, with the greatest effect of deprivation on CHD diagnosis seen in younger women. This observation suggests the need for targeting health promotion and CHD prevention among younger women in deprived areas.